The Separation of the Ukrainian Orthodox Church From the Moscow Patriarchate as a Reflection of Ukrainian State Identity - Civa Syadza Masnun (Journal Of Global Strategic Studies, 2024)
This article discusses the formation of Ukrainian state identity in the struggle for the status of an independent Ukrainian Orthodox Church from the Moscow Patriarchate. Since Ukraine's independence in 1991, the country has had two national churches and one Orthodox church originating from Russia, namely the Ukrainian Orthodox Church-Moscow Patriarchate. The presence of the Ukrainian Orthodox Church-Moscow Patriarchate prompted national church figures to establish an independent (autocephalous) church to become a truly independent country without Russian oversight. However, establishing this church was difficult due to Russian intervention until events occurred that successfully pushed for the ratification of Autocephaly status in 2019. Using Ted Hopf's Constructivism theory regarding identity formed from a country's interaction with external actors and its internal construction, this article examines events between Ukraine and Russia and the social construction within Ukraine. It also highlights the strong public opinion, church actions, and government actions unified in one identity: an independent Ukrainian Orthodox Church.